2016
DOI: 10.1007/s00442-016-3795-y
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of symbiont diversity in freshwater snails: a comparative analysis of resource availability, community heterogeneity, and colonization opportunities

Abstract: Decades of community ecology research have highlighted the importance of resource availability, habitat heterogeneity, and colonization opportunities in driving biodiversity. Less clear, however, is whether a similar suite of factors explains the diversity of symbionts. Here, we used a hierarchical dataset involving 12,712 freshwater snail hosts representing five species to test the relative importance of potential factors in driving symbiont richness. Specifically, we used model selection to assess the explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…(mix of P. acuta and P. gyrina ), of which H. trivolvis and Physa spp. function as first intermediate hosts for many of the trematode species (McCaffrey & Johnson 2017). Amphibian richness at each site ranged from 1 to all 6 species with a mean of 3.1, while snail richness ranged from 0 to 5 taxa, with a mean of 2.1.…”
Section: Resultsmentioning
confidence: 99%
“…(mix of P. acuta and P. gyrina ), of which H. trivolvis and Physa spp. function as first intermediate hosts for many of the trematode species (McCaffrey & Johnson 2017). Amphibian richness at each site ranged from 1 to all 6 species with a mean of 3.1, while snail richness ranged from 0 to 5 taxa, with a mean of 2.1.…”
Section: Resultsmentioning
confidence: 99%
“…All ponds were small habitats containing both species of focal amphibian host and the snail species Helisoma trivovlis and Physa spp. ( Physa acuta or Physa gyrina ), which are intermediate hosts for a diversity of trematode species found in amphibians (McCaffrey & Johnson, 2017). Each pond was visited four to five times across the summer, during which we sampled 10–20 individuals of each host species, representing juvenile life stages from post‐hatching to peri‐metamorphosis (Appendix S1: Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting, however, that even the odonates supported fewer parasite taxa than detected in other vertebrate and invertebrate hosts surveyed from these and other similar pond ecosystems. For instance, studies with amphibian, fish, and snail hosts from pond communities have detected anywhere from 12 to 23 macroparasite taxa, compared to the five taxa from odonates in the current study (Muzzall et al 2001, Pulis et al 2011, Johnson et al 2016, McCaffrey and Johnson 2017, Calhoun et al 2018;).…”
Section: Discussionmentioning
confidence: 56%
“…Teasing apart the effect of each level and their interactions will help better understand and predict changes in both parasite communities and parasite populations. For example, McCaffrey and Johnson (2017) demonstrated that freshwater snail symbiont diversity is driven by both host-level effects, such as snail size and abundance, as well as habitat-level effects that reflect both transmission and colonization opportunities. At the habitat-level, snail symbiont richness correlated positively with wetland size, the proximity of nearby ponds, and diversity of the free-living community, likely reflecting opportunities for colonization and the presence of additional hosts necessary for parasite transmission.…”
Section: Introductionmentioning
confidence: 99%